Mesenchymal Stem Cells for Treatment of Coxofemoral Dysplasia in a Dog - Feitosa, Matheus Cândido; Guerrera, Mariane Ubrik; Siqueira, Jackson Oliveira; Feitosa, Roseane Oliveira; Soares, Anísio Francisco; Weinstein, Marcelo Teixeira (Acta Scientiae Veterinariae, 2022)
Background: Coxofemoral dysplasia (CFD) is the abnormal development of the hip joint, mostly affecting large breeds, and is characterized by subluxation or complete luxation of the femoral head. Among the conservative therapeutic options, cell therapies with stem cells for CFD provides potential by the countless possibilities of therapeutic application, especially those related to the chronic and/or degenerative diseases treatment, which could be a key point for the bone and joint repair. The objective was to report a bilateral CFD case in a dog, treated with intra-articular application of mesenchymal stem cells (MSC), with 0, 30, 60 and 90 days, and further evaluations. Case: A 2-year-old male Akita dog was referred to the Veterinary Hospital Harmonia (HVH) located in the city of Recife, Pernambuco, presenting clinical signs of hip pain, lameness and pelvic limbs hopping. By orthopedic examination, pain was observed at the cranial and caudal extension of the pelvic limb, and at flexion, abduction and adduction of the limb, as well as moderate muscle atrophy and presence of joint crackling. By coxofemoral radiography performed in ventrodorsal projection, it were detected bilateral femoral head subluxation, thickening of the femoral neck and the presence of intra-articular osteophytes. These findings are compatible with the degeneration caused by the presence of CFD. Laboratory tests performed such as hemogram and biochemical had no changes. Thus, the patient had intra-articular application of allogeneic MSC, derived from adipose tissue, obtained by private company. For stem cell applications, arthrocentesis of the hip joints was performed one at a time, using a 5 mL syringe and 16G needle for aspiration of 2 mL synovial fluid, for discard and application of stem cells. After aspiration, the syringe containing the MSC were fitted to the 16G needle for the implant. After the final procedure, the patient was moved to the internment division for anesthetic recovery. The animal was clinically assessed on days 0, 30, 60 and 90 following the criteria of locomotion and physical-orthopedic examination, in which the results were interpreted by a numerical scale. Discussion: For locomotion, there were differences for the pattern observed on days 0, 30, 60 and 90, with reduced claudication until walking without changes. There was also a decrease in the range of motion until limitations absent. For the parameters such as functional capacity and claudication at trot, there were reductions from the 30th day, promoting a slightly rigid gait, being noticeable when running. For the clinical parameters used in the physical-orthopedic evaluation, regarding the parameters analysis such as pain, caudal extension, cranial extension, internal rotation, abduction, and adduction, there were differences from the 30th day through pain reduction, remaining on the 60th and 90th days. Regarding the muscle atrophy, a difference was observed in the right pelvic limb on the 60th day, with moderate recovery. In addition, for the station tests and presence of joint crackling in the pelvic joint, there were no differences for the pattern during data collection regarding all evaluations. Those results allow inferring that MSC contributed to the CFD treatment, promoting the reduction of clinical signs and, consequently, providing a better life quality of the patient, which positively characterize it as a modality of treatment. Keywords: veterinary orthopedic, lameness, joint, genetic disease, degenerative disease. Título: Células-tronco mesenquimais para tratamento de displasia coxofemoral em cão Descritores: ortopedia veterinária, claudicação, articulação, doença genética, doença degenerativa.